The R & D of a swimmer training speed navigator based on the 13th FINA World Championships - Hong-chun, Y.; Yi-fan, L.; Kai, S. (Procedia Engineering, 2014)
The distribution of a swimmer's stamina in competitive 200 m race is very important. The performance depends not only on a swimmer's capability, but also on the strategy of stamina allocation across the four segments. In the present research, athletes who had participated in 200 m items in the 13th FINA World championships (2009, Rome) were allocated into three groups based on their performance, and these groups were top-elite swimmers (top 3 in finals), mid-elite swimmers (top 16 in heats) and lower-elite swimmers (bottom 12 in heats) respectively. Data of the segmental time and the time ratios (the percentage of segmental time in one's total time) of the three groups were analyzed. The results showed that the first and second segmental time ratios (STRs) of the top- and mid-elite groups were relatively larger than those of the lower-elite group. But the situation of the last two STRs was opposite. SONI Rebecca (a very famous USA breaststroke swimmer) missed medals of her strongest 200 m breaststroke event due to her too fast velocity in the first and second segments. These suggested that only the proper allocation of four STRs in 200 m items could bring athletes to their highest performance. So it is very important to optimizing the mode of time allocation during daily training, especially for the gifted swimmers lacking experiences.